2001
DOI: 10.1677/joe.0.1700503
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the adrenomedullin binding protein, complement factor H, in the pancreas and its physiological impact on insulin secretion

Abstract: Adrenomedullin (AM) is a ubiquitous peptide hormone which, among other functional roles, reduces insulin secretion in the pancreas. Recently we have described the interaction between AM and the complement regulator protein factor H, which results in mutual modulation of their respective functions. Here we identify the expression of factor H in the cells of the rat pancreatic islets by immunohistochemistry and multiple immunofluorescence followed by confocal microscopy. In addition, double immunogold staining u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…Isolation of islets from exocrine pancreas Pancreatic islets were isolated from four TS þ /À transgenic mice and four wild-type FVB mice as described previously (Martinez et al, 2001). Each mouse was perfused through the heart with Hank's balanced salt solution (HBSS, Sigma) to remove blood from the pancreatic vessels.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of islets from exocrine pancreas Pancreatic islets were isolated from four TS þ /À transgenic mice and four wild-type FVB mice as described previously (Martinez et al, 2001). Each mouse was perfused through the heart with Hank's balanced salt solution (HBSS, Sigma) to remove blood from the pancreatic vessels.…”
Section: Methodsmentioning
confidence: 99%
“…Examples of activity include its capacity to ameliorate regional ischemic events and blood shunting during sepsis by maintaining local tissue oxygen perfusion and blood flow [43], reducing tissue necrosis and apoptosis through AM/AM-BP complex-augmented production of anti-apoptotic BCL-2 cascade factors and concomitantly decreased pro-apoptotic Bax gene expression [44], effects on pancreatic hormone secretion and localized tissue metabolic responses to pancreatic hormones [13,29,30], interactions with the LPS-TNF-␣-nitric oxide cascade [12,13,38], and its effects to neutralize growth and pathogenic activities of both Gram-negative and Gram-positive [8][9][10] bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data derived from mass spectroscopy proteomic analysis of isolated and purified AM-BP has demonstrated that AM-BP and complement factor-H are one and the same [17], and that the initial localization and quantification of AM-BP by 125 I-AM ligand blot [16] coincided with that derivable using Western blot analysis based on antibody against C-F H [30]. Therefore, milk levels of AM-BP were measured by Western blot using rabbit antihuman C-F H (Serotec, Raleigh, NC) as the primary antibody.…”
Section: Western Blot Analysis Of Milk Adrenomedullin Binding Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Basal levels of complement activation have rather beneficial metabolic effects, ranging from stimulation of insulin secretion in pancreatic β-cells (ASP, fH) [41,42] to insulin-like actions with regard to adipocyte maturation and energy regulation (adipsin, ASP, C3a, C5a) [43]. In contrast, increased complement action can contribute to metabolic pathology.…”
Section: Obesity and Cytokines:-mentioning
confidence: 99%